Therapeutic effect of human clonal bone marrow-derived mesenchymal stem cells in severe acute pancreatitis - Jung, Kyung Hee; Yi, TacGhee; Son, Mi Kwon; Song, Sun U.; Hong, Soon-Sun (Archives of pharmacal research, 2015)
Severe acute pancreatitis (SAP), a common necroinflammatory disease initiated by the premature activation of digestive enzymes within the pancreatic acinar cells, is associated with significant morbidity and mortality. In this study, we investigated whether human bone marrow-derived clonal mesenchymal stem cells (hcMSCs), isolated from human bone marrow aspirate according to our newly established isolation protocol, have potential therapeutic effects in SAP. SAP was induced by three intraperitoneal (i.p.) injections of cerulein (100 μg/kg) and sequential LPS (10 mg/kg) in Sprague-Dawley (SD) rats. hcMSCs (1 × 10 6 /head) were infused on 24 h after LPS injection via the tail vein. The rats were sacrificed 3 days after infusion of hcMSCs. We observed that infused hcMSCs reduced the levels of serum amylase and lipase. Infused hcMSCs ameliorated acinar cell necrosis, pancreatic edema, and inflammatory infiltration. Also, infused hcMSCs decreased the level of malondialdehyde, and increased the levels of glutathione peroxidase and superoxide dismutase. The number of TUNEL positive acinar cells was reduced after hcMSCs infusion. In addition, hcMSCs reduced the expression levels of pro-inflammation mediators and cytokines, and increased the expression of SOX9 in SAP. Taken together, hcMSCs could effectively relieve injury of pancreatitis as a promising therapeutics for SAP.